Surface-confined two-step synthesis of the complex (ammine)(meso- tetraphenylporphyrinato)-zinc(II) on Ag(111) - Flechtner, Ken; Kretschmann, Andreas; Bradshaw, Liam R.; Walz, Marie-Madeleine; Steinrück, Hans-Peter; Gottfried, Michael (Journal of Physical Chemistry C, 2007)
We report the first example of a surface-confined two-step synthesis of axially coordinated metalloporphyrin complexes in an ultrahigh vacuum environment. Specifically, a monolayer of tetraphenylporphyrin on an Ag(111) surface was metalated with coadsorbed Zn atoms, and thereafter, NH ligands were attached to the metal centers. The surface reactions were monitored with X-ray photoelectron spectroscopy. The approach outlined in this work can be employed to produce and study adsorbates of various axially coordinated porphyrin complexes, including biologically relevant systems. © 2007 American Chemical Society.